Assessment of indigenous Shaka cattle structural indices reared in Shaka zone, south west Ethiopia. Issue 4 (April 2022) - Masho, Worku; Banerjee, Sandip; Taye, Mestawet; Admasu, Zelalem; Baye, Mekuanent
Abstract: The study encompassed quantitative traits of the Shaka cattle reared in Shaka zone, Anderacha and Masha weredas of south western, Ethiopia. The study covered quantitative parameters which were taken from 240 cows and 120 bulls from randomly slected120 households. The means for the quantitative traits were compared using Duncan's Multiple Range test, the values were considered significant at P < 0.05 and P < 0.01. The results of morphometrical measurements of bulls reared at Masha wereda had wider (P < 0.05) values for their pelvic width and the Chest Depth for the bulls aged ≥7 years was higher (P < 0.01). While the canon bone circumference was also wider when compared to the bulls reared at Anderacha wereda. Contrary the bulls aged ≤5 years and reared at Anderacha wereda had higher (P < 0.05) for Body Weight, Height at Withers and Chest Depth. Morphometrical measurement for cows ≤5 year age group and reared at Masha wereda have longer (P < 0.05) Neck Length and for cows ≥7 years have wider (P < 0.05) Hock Bone Circumference and Pelvic Width. Contrary the cows aged ≤5 years raised at Anderacha wereda has wider (P < 0.05) for Cannon Bone Circumference, and (P < 0.01) for Chest Girth, higher Body Weight, Rump Length, Ear Length, Neck Circumference and Chest Depth. Among the cows aged ≥7 years have longer (P < 0.01) face length and deeper (P < 0.05) Chest. There is a significant difference in the length index (LI2) and body ratio (BR) (P < 0.05) throughout the research locations, with Anderacha wereda having the higher result, and Masha wereda having the higher depth index (DI) and transverse pelvic index (TPI) (P < 0.05).The results of body indices of both sex indicate that, the cattle is suited for grazing in the forest areas and are of dual type. Abstract : Quantitative measurements; Structural indices; Shaka.